2017
DOI: 10.1111/mve.12231
|View full text |Cite
|
Sign up to set email alerts
|

Application of an embryonated chicken egg model to assess the vector competence of Australian Culicoides midges for bluetongue viruses

Abstract: Culicoides biting midges (Diptera: Ceratopogonidae) are vectors of a number of globally important arboviruses that affect livestock, including bluetongue virus (BTV), African horse sickness virus and the recently emerged Schmallenberg virus. In this study, a model using embryonated chicken eggs (ECEs) was utilized to undertake vector competence studies of Australian Culicoides spp. for 13 laboratory-adapted or wild-type virus strains of BTV. A total of 7393 Culicoides brevitarsis were reared from bovine dung, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…Cq values below 25 have been shown in both colony [24] and field-collected [4, 25] specimens to indicate that viral replication has occurred in the insect so the 4 specimens with Cq values less than 25 were considered infected with BTV. These 4 specimens were all collected from Nixi and were all parous females; 2 were identified as C. tainanus , 1 was Culicoides sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cq values below 25 have been shown in both colony [24] and field-collected [4, 25] specimens to indicate that viral replication has occurred in the insect so the 4 specimens with Cq values less than 25 were considered infected with BTV. These 4 specimens were all collected from Nixi and were all parous females; 2 were identified as C. tainanus , 1 was Culicoides sp.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence was measured at the end of each annealing step. Only reactions with Cq values of 25 or lower were regarded as indicative of replication of BTV in the midge [4, 24, 25].…”
Section: Methodsmentioning
confidence: 99%
“…However, we could not apply this ratio in our experiments as this would have excessively reduced the infectivity. Earlier studies have suggested minimal virus titres in the blood meals (C q values below 30 per μl blood or a minimum of 5 log 10 TCID 50 /ml) [ 49 , 79 ]. Thus, 2:1 (BTV-4 and BTV-8) or 1:1 (BTV-1) ratios were used in our experiments to fulfil these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Small invertebrates and small vertebrates were preserved in absolute ethanol. Pooled tissues or whole bodies from ethanol fixed animals were prepared for nucleic acid extraction by first digesting in proteinase K solution as described previously [ 17 ]. Full details of the species, the samples collected and the numbers examined are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%